2021
DOI: 10.2500/aap.2021.42.210069
|View full text |Cite
|
Sign up to set email alerts
|

Allergic reactions and adverse events associated with administration of mRNA-based vaccines. A health-care system experience

Abstract: Background: Adverse reactions, including anaphylaxis, to messenger RNA coronavirus disease 2019 (COVID-19) vaccines rarely occur. Because of the need to administer a timely second dose in subjects who reported a reaction to their first dose, a panel of health-care professionals developed a safe triage of the employees and health care providers (EHCP) at a large health-care system to consider administration of future dosing. Methods: There were 28,544 EHCPs who received their first dose of COVID-19 vaccines b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…However, a report from Ontario in period between December 13, 2020 and March 6, 2021 noted anaphylaxis cases the rates of 32.7 and 38.0 per million doses administered of mRNA-1273 and BNT162b2, respectively [ 41 ]. Among health care providers from Baylor Scott and White Health from Texas, which were vaccinated with first dose, only 3 persons had anaphylaxis what corresponds to 0.01% of vaccinated medical staff members [ 42 ]. In overall, in U.S. after first month of vaccination in period between December 14, 2020 and January 13, 2021, 4.5 per million cases of anaphylaxis after doses administered of both mRNA vaccines have been reported [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a report from Ontario in period between December 13, 2020 and March 6, 2021 noted anaphylaxis cases the rates of 32.7 and 38.0 per million doses administered of mRNA-1273 and BNT162b2, respectively [ 41 ]. Among health care providers from Baylor Scott and White Health from Texas, which were vaccinated with first dose, only 3 persons had anaphylaxis what corresponds to 0.01% of vaccinated medical staff members [ 42 ]. In overall, in U.S. after first month of vaccination in period between December 14, 2020 and January 13, 2021, 4.5 per million cases of anaphylaxis after doses administered of both mRNA vaccines have been reported [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another observational study of 28,544 employees and health care providers receiving a first dose of a mRNA-based vaccine in the period between December 15, 2020, and March 8, 2021, reported 1253 vaccine-related adverse reactions. For 113 subjects, the experts required further evaluation before receiving the second dose, since three persons reported symptoms that were judged to be consistent with anaphylaxis [20].…”
Section: Evidence From Post-marketing Observational Studiesmentioning
confidence: 99%
“…Only 41 studies met our inclusion criteria 22,61–100 ; these consisted of 18 case series/reports, 18 cohort studies without control groups, and 4 cohort studies with control groups, one of which was a double‐blinded randomized clinical trial. The last study, Kaplan et al, 79 contained both a cohort analysis and a case series.…”
Section: Resultsmentioning
confidence: 99%
“…Anaphylaxis was also more common in women, with 76 of the case series being female. Cohort studies, such as Arroliga et al 91 and Klein et al 90 also reported that the vast majority of anaphylactic cases occurred in females. Moreover, they suggested that this difference in adverse events could be due to genetic differences, hormonal influences, environmental or immunological variance between men and women.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation